1986
DOI: 10.2136/sssaj1986.03615995005000030023x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lime and Organic Matter on Soybean Seedlings Grown in Aluminum‐toxic Soil

Abstract: Organic matter is believed to be able to reduce Al toxicity in Ultisols. Since little information is available to substantiate this hypothesis, a greenhouse experiment was conducted to compare the effects of organic matter and lime on soybean [Glycine max (L.) Merr.] plants grown under increasing Al stress in a Bradson (Typic Hapludults) soil. Treatments, replicated three times, were 0, 25, 50, and 100 mg Al kg−1 pot−1, 0, 5, and 10% wheat (Triticum aestivum L.) straw, and the equivalent of 0, 1, and 2 Mg CaCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…In fact, amendments with chicken manure or sewage sludge often outyielded those with Ca(OH) 2 It was also observed that manure-fertilized plants contained more Ca and less…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, amendments with chicken manure or sewage sludge often outyielded those with Ca(OH) 2 It was also observed that manure-fertilized plants contained more Ca and less…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that the addition of green manures and animal wastes reduces Al toxicity and increases crop yields (2,3,4,5). Complexation of soil solution Al by decomposition products of organic residues has been implicated in Al detoxification (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…When Al +3 is held tightly by the organic matter, the KCl 1N extraction solution can only displace it partially (Hargrove and Thomas, 1981;Ahmad and Tan, 1986). However, others extraction solutions were able to extract more Al +3 , especially from the soil organic matter and in the soil with pH about 4.8, which was higher limit for Al +3 extraction by KCl 1.0N (Hargrove and Thomas, 1981;García-Rodeja et al, 2004).…”
Section: Magnesiummentioning
confidence: 93%
“…Once again the corncob compost treatment did not drastically alter the soil pH, but induced a better dry matter yield of 2.11 g-plant 1 with the CC-3 treatment which could be partially explained by an increased plant P uptake of 6.26 mgplant 1 (Table 1). Ahmad and Tan (1986) also found that soil treatments with wheat straw produced taller soybean plants and greater dry weights of roots than treatment with lime alone.…”
Section: Dry Weight Yield Soil Ph and Plant Phosphorus Uptakementioning
confidence: 82%